2022
DOI: 10.1002/aepp.13246
|View full text |Cite
|
Sign up to set email alerts
|

The farm to fork strategy and the digital transformation of the agrifood sector—An assessment from the perspective of innovation systems

Abstract: The article assesses the European Union's Farm to Fork (F2F) strategy from the perspective of innovation systems, focusing on digital technologies in agriculture. It employs the Technical Innovation Systems framework to analyze how the policies proposed in the F2Fstrategy affect essential functions of the innovation system. The analysis shows that the F2F strategy significantly contributes to innovation system performance by providing a clear and coherent agenda and various concrete measures designed to suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 61 publications
0
6
0
2
Order By: Relevance
“…Azonban, ahogyan azt maga a stratégia is elismeri és különböző hatásvizsgálatok (Barreiro-Hurle et al, 2021;Beckman et al, 2020;Henning et al, 2021;Noleppa és Cartsburg, 2021) kimutatták, a politikai akarat önmagában nem fogja elérni az ambiciózus célokat. A siker nagymértékben függ az innovációtól, mind a meglévő innovációk skálázásától, mind a teljesen új innovációk kifejlesztésétől (Reinhardt, 2022) szertani és kivitelezési gyakorlat az eredeti tanulmányban lelhető fel.…”
Section: Szakirodalmi Feldolgozásunclassified
“…Azonban, ahogyan azt maga a stratégia is elismeri és különböző hatásvizsgálatok (Barreiro-Hurle et al, 2021;Beckman et al, 2020;Henning et al, 2021;Noleppa és Cartsburg, 2021) kimutatták, a politikai akarat önmagában nem fogja elérni az ambiciózus célokat. A siker nagymértékben függ az innovációtól, mind a meglévő innovációk skálázásától, mind a teljesen új innovációk kifejlesztésétől (Reinhardt, 2022) szertani és kivitelezési gyakorlat az eredeti tanulmányban lelhető fel.…”
Section: Szakirodalmi Feldolgozásunclassified
“…For example, the use of modern technologies to improve animal welfare was suggested merely as one of the actions, indicating that the legislative proposals fall short of seriously considering innovation for the improvement of animal welfare. This could be viewed in light of Reinhardt's findings in this special issue that the strategy fails to propose proper market incentives for innovation and punishes those who fall behind in adopting innovative approaches in agriculture (Reinhardt, 2023), including animal welfare.…”
Section: The European Commission's Revision Of Animal Welfare Legisla...mentioning
confidence: 99%
“…Despite soliciting layperson's opinions, it is regularly questioned whether labeling can contribute to sustainability by encouraging sustainable consumption (Stein & de Lima, 2021). On this issue, a subgroup will assist the Commission in collecting data and opinions, assuming a behavioral perspective as suggested by Purnhagen in this special issue (Purnhagen, 2022), and hopefully a more robust methodology than that employed in the consultation (European Commission, 2021b).…”
Section: The European Commission's Revision Of Animal Welfare Legisla...mentioning
confidence: 99%
“…However, as the strategy itself acknowledges and various impact evaluations (Barreiro-Hurle et al, 2021;Beckman et al, 2020;Henning et al, 2021;Noleppa and Cartsburg, 2021) have shown, political will alone will not achieve ambitious targets. Success depends to a large extent on innovation, both scaling existing innovations and developing entirely new ones (Reinhardt, 2022). To support these, consider first the results presented by Beckman et al (2020) The estimated effects in the EU are clearly projected to be a fall in producer incomes in the range of 8-16 percentage points, an increase in consumer spending in the range of USD 153-651 per capita per year, and a fall in GDP of USD 71-186 billion.…”
Section: Literature Processingmentioning
confidence: 99%